2014
DOI: 10.1016/j.actpsy.2013.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Duration perception in crossmodally-defined intervals

Abstract: How humans perform duration judgments with multisensory stimuli is an ongoing debate. Here, we investigated how sub-second duration judgments are achieved by asking participants to compare the duration of a continuous sound to the duration of an empty interval in which onset and offset were marked by signals of different modalities using all combinations of visual, auditory and tactile stimuli. The pattern of perceived durations across five stimulus durations (ranging from 100 ms to 900 ms) follows the Vierord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 25 publications
4
21
0
1
Order By: Relevance
“…The stability of the Weber fraction over time reported by Mayer et al (2014) is a bit surprising considering the data reported by Grondin (1996) for intermodal intervals lasting 0.125, 0.25, 0.5, 1, 2, or 4 s. In this study, AV and VA intervals were used. There were 36 sessions (3 per experimental condition) lasting about 30 (at 0.125 s) to 65 min (at 4 s).…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…The stability of the Weber fraction over time reported by Mayer et al (2014) is a bit surprising considering the data reported by Grondin (1996) for intermodal intervals lasting 0.125, 0.25, 0.5, 1, 2, or 4 s. In this study, AV and VA intervals were used. There were 36 sessions (3 per experimental condition) lasting about 30 (at 0.125 s) to 65 min (at 4 s).…”
mentioning
confidence: 63%
“…The recent data reported by Mayer et al (2014) are also interesting as they describe the discrimination levels. In the VA and AV conditions, the Weber fractions are roughly the same, and vary from 30% at 0.1 s to slightly above 20% at 0.9 s. The results are essentially the same when auditory and tactile stimuli combinations are used, with the exception that performances are generally better when the auditory marker is presented first, especially at 0.1 s (above 40% in TA).…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Furthermore, a related and well-known effect referred to as “Vierordt’s law” suggests that these patterns are even seen in healthy subjects (Vierordt 1868), albeit to a lesser degree. Specifically, when subjects are asked to make duration judgments regarding multiple intervals across different trials, shorter and longer durations tend to be under and over-estimated, respectively (Bausenhart et al 2014; Mayer et al 2014). This pattern has been observed across a variety of timing tasks and sensory modalities (for discussion see Lejeune and Wearden 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Timing is more precise when stimuli are presented in the auditory rather than the visual modality (Grondin, 1993;Grondin, Meilleur-Wells, Ouellette, & Macar, 1998;Mayer, Di Luca, & Ernst, 2014;Rammsayer, Buttkus, & Altenmüller, 2012;Ulrich et al, 2006), and this auditory superiority might be due to the automaticity of temporal processing in audition.…”
mentioning
confidence: 99%